(untitled) (SAARC Journal of Agriculture, 2021)
Sixteen tomato varieties were evaluated against fruit borer (Helicoverpa armigera) to find out borer resistant tomato varieties. The eight varieties were collected from Bangladesh Agricultural Research Institute (BARI) and eight varieties from the farmer’s field of South-west Bangladesh. This field experiment was conducted in a protected net house suitable for inoculation of the fruit borer at germplasm center of Khulna University for two years (2018 and 2019). Data were collected on fruit physical characters, and borer infestation. The genotypes BARI Tomato-18, BARI Tomato-16, Ruma-VF, Pusa Ruby and Guli had the minimum weight of infested fruit (3.57%, 3.63%, 4.83%, 7.17% and 7.67%, respectively ) as well as the minimum number of infested fruits (both were bellow10%) with the minimum number of larvae of H. armigera (0.23, 0.28, 0.27, 0.54 and 0.60 larvae plant-1, respectively). BARI Tomato-8, BARI Tomato-17 and Paltola were found as more susceptible (29.71%, 26.01% and 28.95% infestation, respectively) than the others. Maximum fruit weight plant-1 was recorded from the genotypes BARI Tomato-18, BARI Tomato-19, Surakha and Paltola (2603g, 2687g, 2755g and 2731g respectively) and among these BARI Tomato-18 and Suraksa gave maximum fresh yield plant-1 (2512.77 g and 2476.53 g, respectively). The fruit infestation rate was significantly and positively correlated with fruit weight loss plant-1 (r = 0.971), larvae plant-1 (r = 0.789), fruit diameter (r = 0.567) and individual fruit weight (r = 0.545). On the other hand, the fruit shape index (r = -0.44) and the number of fruit plant-1 (r = -0.498) were significant and negatively correlated with fruit infestation rate. It could be concluded that BARI Tomato-18 and BARI Tomato-16 are resistant as well as high yielding varieties. SAARC J. Agri., 18(2): 87-99 (2020)